1999
DOI: 10.1292/jvms.61.13
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Metabolic Adaptations in Horses Competing in Cross-Country Events.

Abstract: ABSTRACT. The cardiovascular and metabolic response to two cross-country events (CC*: preliminary level and CC*** advanced level) were analysed in 8 male eventing horses (4 Anglo-Hunter and 4 Anglo-Arabian). This study focused on the establishment of the main metabolic pathways involved in the muscle energy resynthesis during the competitions. Heart rate (HR) was recorded throughout the CC events. Jugular venous blood samples were withdrawn before the warm-up period, immediately after the competitions and at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
2
28
0
3
Order By: Relevance
“…One of the most important biochemical parameters in Sport Medicine is lactate (LA), a metabolite derived from glycolytic pathways, which is an indicator for the onset of fatigue (Munoz et al, 1999a;Rovira et al, 2007b). Hyperlactacidemia has been implied in the development of rhabdomyolysis and exhaustion in dogs (Brzezinska, 1987;Breitschwerdt et al, 1992).…”
mentioning
confidence: 99%
“…One of the most important biochemical parameters in Sport Medicine is lactate (LA), a metabolite derived from glycolytic pathways, which is an indicator for the onset of fatigue (Munoz et al, 1999a;Rovira et al, 2007b). Hyperlactacidemia has been implied in the development of rhabdomyolysis and exhaustion in dogs (Brzezinska, 1987;Breitschwerdt et al, 1992).…”
mentioning
confidence: 99%
“…Increases in plasma proteins with an increased capillary refill time and a decreased skin turgor might be attributed to the acute dehydration. The increase in serum protein concentrations after exercise has been observed in other equestrian competitions such as polo [14,15] , flat racing [26] , cross country [10] and endurance [24] . It has been reported that hyperproteinemia occurs in athletic horse as a result of dehydration [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these changes have been studied in equestrian sports such as flat racing [2][3][4] , endurance [5][6][7] , show jumping [8,9] , eventing [10] , reining [11] , marcha [12] , cavalcade [13] , and polo [14,15] . However, to the best to our knowledge, there is no such a study focused on jereed horses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be assumed that the examined group of horses is typical, i.e. within the HR referential ranges for this type of effort (Muñoz et al 1999). …”
Section: Discussionmentioning
confidence: 99%